Faktor-Faktor yang Berhubungan dengan Kualitas Hidup Penderita Diabetes Melitus Tipe 2 Usia Produktif di Puskesmas Meuraxa Banda Aceh 2025 - Raudhah Rizkina; Asnawi Abdullah; Nopa Arlianti (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
As a chronic pathology, diabetes mellitus (DM) exhibits a surging prevalence that severely deteriorates the well-being and quality of life of affected individuals. This investigation sought to analyze the specific determinants influencing the quality of life among productive-age individuals (ranging from 15 to 64 years) diagnosed with type 2 DM within the administrative territory of the Meuraxa Public Health Center, Banda Aceh, in 2025. Professionally, this research integrated a descriptive analytic framework utilizing a cross-sectional design. From a total population of 391 type 2 DM patients, a cohort of 80 participants was selected via an accidental sampling strategy. Empirical data were gathered through structured questionnaire-guided interviews and subsequently processed using univariate and bivariate statistical evaluations within the SPSS software environment. The descriptive univariate assessments indicated that a vast majority of the subjects experienced a moderate quality of life (80.0%). Regarding independent variables, 45.0% demonstrated negative attitudes, 26.3% possessed deficient knowledge, 50.0% had a long-standing disease duration, 48.8% reported a history of medication-induced adverse effects, and 51.3% presented with a history of diabetic ulcerations or wounds. Furthermore, the inferential bivariate modeling demonstrated a statistically significant correlation between quality of life and three major indicators: patient attitude (p = 0.003), health literacy or knowledge (p = 0.015), and wound history (p = 0.048). Conversely, no significant associations were observed for illness duration (p = 0.090) or the experience of pharmaceutical side effects (p = 0.317). To conclude, personal attitude, cognitive knowledge, and clinical wound history stand as pivotal elements dictating the quality of life in working-age type 2 DM patients. Consequently, systematic health counseling and targeted complication mitigation strategies must be intensified to optimize patient well-being.